P-185 The migration speed of nucleolar precursor bodies in pronuclei affects in vitro fertilization-derived human embryo ploidy status. (30th June 2022) - Inoue, T; Taguchi, S; Uemura, M; Tsujimoto, Y; Yamashita, Y
Abstract: Study question: Does the migration speed of nucleolar precursor bodies (NPBs) in male and female pronuclei (mPN and fPN) affect in vitro fertilization (IVF)-derived embryo ploidy status? Summary answer: The NPB migration speed in mPN impacts the IVF-derived human embryo ploidy status and this indicator could be an attractive marker for noninvasive embryo selection. What is known already: NPBs are not considered as simple nucleolar components transmitted from an oocyte to an embryo, and they could participate in genome remodeling during embryo development. NPBs are essential only shortly after fertilization, suggesting that they may actively participate in centromeric chromatin establishment. A previous study demonstrated that NPBs migrated faster in intracytoplasmic sperm injection-derived zygotes having the potential to develop into a blastocyst and eventually into a baby (Inoue et al ., 2021). However, the relationship between NPB migration speed and IVF-derived embryo ploidy status is unclear. Study design, size, duration: The relationship between the NPB migration speed and embryo ploidy status was retrospectively analyzed in patients with recurrent assisted reproductive technology failure (euploid n  =18; aneuploid n  =19; and total = 219 NPBs). Archived time-lapse videos (images were recorded every 5 min; Geri+) from incubation after IVF were retrieved after the patients were identified for the study, and the NPB migration speed was analyzed. The retrospective analyses were performed with the patient's identities masked. Participants/materials, setting, methods: mPN and fPN were identified by appearance location in a zygote (fPN appearance is just below the polar bodies). The mPN, fPN, and 2–3 NPBs/PN central coordinates were measured by Kinovea (motion capture software). Their central coordinates were confirmed/revised every image and were decided. The migration distance of NPBs between two sequential images was calculated as the standard of the central PN coordinates. Thereafter, the migration speed of NPBs was calculated. Main results and the role of chance: Both NPB speeds were significantly faster in the euploid than in the aneuploid groups (mPN: 4.08±0.61 vs. 3.54±0.54 µm/h, P  =0.003, power [1-β]: 0.999, fPN: 4.03±0.89 vs. 3.26±0.45 µm/h, P  <0.003, 1-β: 0.987). The NPB speed in mPN was correlated with that in fPN ( rs  =0.523, P  =0.001). The ploidy status was related to the NPB speeds in mPN and fPN ( P  <0.05) in univariate logistic analysis including male/female ages, ICM/TE grades, and 29 morphokinetic parameters. The factors associated with ploidy status were the NPB speed in mPN (odds ratio [OR], 10.2; 95% confidence interval [CI], 1.90–54.90; P  =0.007) and female age (OR, 0.8; 95%CI, 0.64–0.98; P  =0.03) in multivariate logistic analysis. The cutoff value for the NPB speeds in mPN and fPN were 3.65 μm/h (specificity, 73.7%; sensitivity, 77.8%; AUC, 0.78; 95%CI, 0.62–0.93) and 3.77 μm/h (specificity, 89.5%; sensitivity, 66.7%; AUC, 0.78; 95%CI, 0.62–0.94). When the zygotes were categorized by their cutoff values, the euploid rate in zygotes with NPB speeds greater than the cutoff value was significantly higher than that in zygotes with the speeds less than the cutoff value (mPN = 73.7% vs. 22.2% [ P  =0.003]; fPN = 85.7% vs. 26.1% [ P  <0.001]). Limitations, reasons for caution: The NPB migration in the z -axis direction could not be analyzed. NPB tracking could not be performed when NPBs were large in number or drastically moved. Our findings should help in elucidating the relationship, although they did not completely explain the relationship between NPB migration and embryo development. Wider implications of the findings: The migration speed of NPBs impacts human embryo ploidy status. NPB migration speed may add clinical value for embryo selection, which may be associated with live birth, and consequently, the time of the live birth could be shorter. The indicator could be an attractive marker for noninvasive embryo selection. Trial registration number: Not applicable